Diversities Old and New: Migration and Socio-Spatial Patterns in New York, Singapore and Johannesburg - Vertovec, S. (Palgrave Macmillan, 2020)
Diversities Old and New provides comparative analyses of new urban patterns that arise under conditions of rapid, migration-driven diversification, including transformations of social categories, social relations and public spaces. Ethnographic findings in neighbourhoods of New York, Singapore and Johannesburg are presented